Hereditary Long Q-T Without Congenital Deafness (Romano-Ward) Syndrome - Bambang Madiyono; Alinda Rubiati Wibowo; Ismet N. Oesman; Sudigdo Sastroasmoro; Sukman Tulus Putra; Najib Advani (Paediatrica Indonesiana, 1994)
We report a case o fhereditary long Q-T syndrome without congenital deafness (Romano-Ward syndrome). In four members of a family, a father and his daughters, the Q-T intervals on the EKG were found to be prolonged. There were no other accompanying familial anomalies such as deafness or a tendency to extracellular hypokalemia The youngest daughter which had the longest. Q-T interval had several Adams-Stokes attacks, and died in the last attack at the age of 23 months. Her two older siblings died at the age of 15 and 10 months with the same typical clinical histories. The eldest daughter, a 12-year old girl, has no clinical symptoms at all, while the fourth child, 5-yeltr old girl has several occasions of near fainting attacks. The EKG of the father showed several runs of supraventricular premature contractions that ceased spontaneously, besides evidence of the prolongation of Q-T interval. The beta-adrenergic blocking drug (propranalol) given in a relatively small maintenance dose, proved to be effective in preventing attacks of the father and the fourth child, despite the unchanged prolongation of the Q-T interval.